CEO CHARACTERISTICS AND FINANCIAL PERFORMANCE OF LISTED DMBS IN NIGERIA - Florence Bosede Ajagbonna; Benjamin Kumai Gugong; Augustine Ayuba; Idris Mohammed; Isuwa Dauda (Gusau Journal of Accounting and Finance, 2024)
This study seeks to investigate the effect of Chief executive officer’s characteristic on financial performance of listed deposit money banks in Nigeria. The study adopts correlation and ex-post facto as research design. The population of the study consists of 16 listed deposit money banks in Nigeria and the sample of the study consists of 14 listed deposit money banks in Nigeria. Census sampling technique is employed. Multiple regression model based on pooled ordinary lease square robust test is adopted to analyze the panel data obtained from audited financial statements of the sampled listed deposit money banks between 2012- 2021. The study reveals that Chief executive officer’s tenure has a negative and significant influence on financial performance, while, Chief executive officer’s gender was discovered to have a positive effect on financial performance. It is recommended that the board members should initiate coherent and integrated and policies towards reducing tenure ship of the Chief executive officers below the average which will ultimately improve the financial performance of the banks. Also, the board should initiate policy that will always consider female gender in the appointment of Chief executive officer’s positions considering the risk appetite of the female Chief executive officer’s particularly in risk and financial management of the banks which will also influence the financial performance of the listed deposit money banks in Nigeria.